Comparison of the Effects of Different Light Sources on Reading and Optical Performance (Medical Forum Monthly, 2024)
Objective: To compare the effects of different light sources on reading and optical performance.Study Design: Prospective observational study.Place and Duration of Study: This study was conducted at the Mayo Hospital, Lahore from June 15, 2017 to December 15, 2017.Materials and Methods: Eighty four participants (42 males and 42 females) were presented passages to read under four lighting conditions, followed by contrast assessment. Color vision was assessed with 17 Ishihara pseudo-isochromatic slides. Fifteen minutes were given for adaptation under all four lights. All the data was put in SPSS v.23 software. Data was analyzed with one way ANOVA and Friedman test. P value < 0.05 was considered statistically significant.Results: The difference of reading rate was statistically significant (p<0.001) under various light sources in both male and female subjects. In males, reading rate was fastest under compact fluorescence light while in females, reading rate was fastest under light emitting diode light. One way analysis of variance with Friedman’s test showed a significant relevance between visual performance and various illumination sources in males (P <0.001) and females (P <0.001)Conclusion: We concluded that there was a significant association between reading performance and the type of illumination. Most male suggested the use of compact fluorescent light and most females suggested the use of light emitting diodes as a source of light. Tungsten bulbs were the least recommended source of light for study purpose. Fluorescent and light emitting diode lights are the suitable sources of light to perform study tasks.